Home A Summary of Factoring Polynomials Factoring The Difference of 2 Squares Factoring Trinomials Quadratic Expressions Factoring Trinomials The 7 Forms of Factoring Factoring Trinomials Finding The Greatest Common Factor (GCF) Factoring Trinomials Quadratic Expressions Factoring simple expressions Polynomials Factoring Polynomials Fractoring Polynomials Other Math Resources Factoring Polynomials Polynomials Finding the Greatest Common Factor (GCF) Factoring Trinomials Finding the Least Common Multiples
Try the Free Math Solver or Scroll down to Tutorials!

 Depdendent Variable

 Number of equations to solve: 23456789
 Equ. #1:
 Equ. #2:

 Equ. #3:

 Equ. #4:

 Equ. #5:

 Equ. #6:

 Equ. #7:

 Equ. #8:

 Equ. #9:

 Solve for:

 Dependent Variable

 Number of inequalities to solve: 23456789
 Ineq. #1:
 Ineq. #2:

 Ineq. #3:

 Ineq. #4:

 Ineq. #5:

 Ineq. #6:

 Ineq. #7:

 Ineq. #8:

 Ineq. #9:

 Solve for:

 Please use this form if you would like to have this math solver on your website, free of charge. Name: Email: Your Website: Msg:

## Complete Squares

Exercise

Write each of the following as a complete square.

(a) x - 10x + 25

(b) z + 8z + 16

(c) w - w + 1/4

(d) y + 5y + 25/4

Solution

(a) Comparing x - 2ax + a with x - 10x + 25 we see that 2a = 10 , and a = 25 . Thus a = 5 is the solution. It may easily be checked that

(x - 5) = x - 10x + 25 .

(b) Comparing z - 2az + a with z + 8z + 16, it follows that -2a = 8 , and a = 16 . In this case a = -4. Checking

(z - ( -4)) = (z + 4) = z + 8z + 16 .

(c) Comparing w - 2aw + a with w - w + 1/4, we must have -2a = -1 , and a = 4 . In this case a = 1/2 , and

It is now easy to check that

(d) Comparing y - 2ay + a with y + 5y + 25/4 we must have -2a = 5 , and a = 25/4 . From this it must follow that a = -5/2 .

Note that

It is now easy to check that

Quiz

Which of the following quadratic expressions is a complete square?

(a) z + 3 z - 9 /4 (b) z + 3 z + 9 /2 (c) z - 3 z + 9 /4 (d) z - 3 z + 9 /2

Solution

Comparing z - 3z + 9/4 with the general form of a complete square (z - a) = z - 2az + a

if -2a = -3 then ,

and

Now it is easily checked that